EEG findings in acutely ill patients investigated for SARS‐CoV‐2/COVID‐19: A small case series preliminary report. Issue 2 (17th May 2020) - Galanopoulou, Aristea S.; Ferastraoaru, Victor; Correa, Daniel J.; Cherian, Koshi; Duberstein, Susan; Gursky, Jonathan; Hanumanthu, Rajani; Hung, Christine; Molinero, Isaac; Khodakivska, Olga; Legatt, Alan D.; Patel, Puja; et al.
Abstract: Objective: Acute encephalopathy may occur in COVID‐19‐infected patients. We investigated whether medically indicated EEGs performed in acutely ill patients under investigation (PUIs) for COVID‐19 report epileptiform abnormalities and whether these are more prevalent in COVID‐19 positive than negative patients. Methods: In this retrospective case series, adult COVID‐19 inpatient PUIs underwent EEGs for acute encephalopathy and/or seizure‐like events. PUIs had 8‐channel headband EEGs (Ceribell; 20 COVID‐19 positive, 6 COVID‐19 negative); 2 more COVID‐19 patients had routine EEGs. Overall, 26 Ceribell EEGs, 4 routine and 7 continuous EEG studies were reviewed. EEGs were interpreted by board‐certified clinical neurophysiologists (n = 16). EEG findings were correlated with demographic data, clinical presentation and history, and medication usage. Fisher's exact test was used. Results: We included 28 COVID‐19 PUIs (30‐83 years old), of whom 22 tested positive (63.6% males) and 6 tested negative (33.3% male). The most common indications for EEG, among COVID‐19‐positive vs COVID‐19‐negative patients, respectively, were new onset encephalopathy (68.2% vs 33.3%) and seizure‐like events (14/22, 63.6%; 2/6, 33.3%), even among patients without prior history of seizures (11/17, 64.7%; 2/6, 33.3%). Sporadic epileptiform discharges (EDs) were present in 40.9% of COVID‐19‐positive and 16.7% of COVID‐19‐negative patients; frontal sharp waves were reported in 8/9 (88.9%) of COVID‐19‐positive patients with EDs and in 1/1 of COVID‐19‐negative patient with EDs. No electrographic seizures were captured, but 19/22 COVID‐19‐positive and 6/6 COVID‐19‐negative patients were given antiseizure medications and/or sedatives before the EEG. Significance: This is the first preliminary report of EDs in the EEG of acutely ill COVID‐19‐positive patients with encephalopathy or suspected clinical seizures. EDs are relatively common in this cohort and typically appear as frontal sharp waves. Further studies are needed to confirm these findings and evaluate the potential direct or indirect effects of COVID‐19 on activating epileptic activity.